1992
DOI: 10.1099/0022-1317-73-4-1025
|View full text |Cite
|
Sign up to set email alerts
|

Further analysis of nucleic acids in purified scrapie prion preparations by improved return refocusing gel electrophoresis

Abstract: Although increasingly unlikely, the possibility of a scrapie-specific nucleic acid carried by infectious prion particles is still unresolved. Return refocusing gel electrophoresis was developed to detect homogeneous and heterogeneous nucleic acids extracted from highly purified scrapie prion preparations. This method was improved with respect to the size range from 13 to 1100 nucleotides (nt) over which analyses could be performed. The yield of nucleic acid, particularly of small DNA oligonucleotides and polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0
3

Year Published

1993
1993
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(69 citation statements)
references
References 11 publications
1
64
0
3
Order By: Relevance
“…These experiments show that the infectious agent is physically associated with PrP sc or a molecule very similar to it, but do not preclude the association of the PrP-derived molecule with another component. It has, however, been shown that highly purified prion preparations contain less than one molecule of nucleic acid larger than about 100 nucleotides [33].…”
Section: Physical Linkage Of Prp Sc and Prionsmentioning
confidence: 99%
“…These experiments show that the infectious agent is physically associated with PrP sc or a molecule very similar to it, but do not preclude the association of the PrP-derived molecule with another component. It has, however, been shown that highly purified prion preparations contain less than one molecule of nucleic acid larger than about 100 nucleotides [33].…”
Section: Physical Linkage Of Prp Sc and Prionsmentioning
confidence: 99%
“…These results, and numerous unsuccessful attempts to detect a scrapiespecific nucleic acid (36)(37)(38)(39)(40), militate against a foreign nucleic acid as an essential component of the "infectious" prion, despite proposals to the contrary (32, [41][42][43] …”
Section: Methodsmentioning
confidence: 99%
“…The key molecular event in prion diseases is the conformational change of a host-encoded prion protein, denoted as PrP C , into the disease-causing isoform, PrP Sc (1). Because prions do not contain any genetic information in the form of nucleic acid (2,3), the information for prions is enciphered in the structure of the pathological isoform. Prion replication occurs by converting PrP C to PrP Sc ; the pool of PrP C is replenished by the cellular synthesis of PrP C .…”
Section: P Rion Diseases Are Fatal Neurodegenerative Diseases That Imentioning
confidence: 99%